Niños de la Amazonía. Una experiencia de trabajo conjunto por una mejor educación para los niños y las niñas asháninkas de la selva central del Perú - Moromizato Izu, Regina (2011)
Children of the Amazon. A cooperative work experience to improve the quality of early childhood education in the Amazon of PerúThis article describes and analyzes the experience of three years of implementation of the Amazon Children Project, which promoted the formation and strengthening of a social platform, formed by allies who energized the actions of the project.This collective effort had as main objective to contribute in the development and learning for children from 3 to 8 years, who live in Ashaninka´s communities in the central jungle from the improvement in the quality of education, facilitatingthe process of transition between educational levels.